Good omens : the nice and accurate prophecies of Agnes Nutter, witch - Gaiman, Neil.; Pratchett, Terry (London : Corgi Books, 1990)
When Agnes Nutter predicts that the end of the world is days away, the demon Crowley and his angel friend, Aziraphale, team up to save humankind.
Adult.
Adult
Keywords: Angels -- Fiction; Antichrist -- Fiction; End of the world -- Fiction; Angels -- Fiction; Antichrist -- Fiction; Humorous fiction; Fantastic fiction; Fantastic fiction; Humorous fiction